A Classical Review On Bhagandar (Fistula in ano) - Sahu, Shraddha; Patel, Shekhar; Kumar, Ashok; Singh, Narinder (International Research Journal of Ayurveda & Yoga, 2020)
The complete and holistic description of Bhagandar (Fistula in ano) has been explained in classical Ayurvedic texts. It is a common disease in the anorectal region. The Father of the Surgery, Acharya Sushruta, includes this disease under Ashtamahagada . At first it appears as a pidika around guda and when it bursts, it is called Bhagandara. Bhagandar’s clinical features described in Ayurvedic texts perfectly resemble that of ’Fistula in ano. Due to recurrence the treatment is very difficult. In modern surgery, various treatment methods are available for the treatment of fistula in ano. Treating fistula in ano is a big challenge to the proctologists . In addition to the various treatment modalities available, Ksharasutra has been known to be more effective among all Ayurvedic parasurgical procedures in treating Fistula in ano. Ksharasutra has been shown to be more effective therapy. Fistula in ano induces discomfort and pain in performing day-to-day activities . In this review, the article describes the pathophysiology, methods and treatment options for Fistula in ano both in Ayurveda and Western Medical sciences